Repentance at Qumran : the penitential framework of religious experience in the Dead Sea Scrolls - Jason, Mark A. (Minneapolis. : Fortress Press., 2015)
Mark A. Jason offers a detailed investigation of the place of repentance in the Dead Sea Scrolls, addressing a significant lacuna in Qumran scholarship. Normally, when the belief system of the community is examined, "repentance" is usually taken for granted or relegated to a peripheral position. By careful attention to key texts, Jason establishes the importance of repentance as a fundamental way of structuring and describing religious experience within the Qumran community. Repentance was important not only for entry into the community and covenant but also for daily governance and cultic activities, and even for authenticating understanding of the end times. Jason shows, then, that repentance was a central and decisive element in shaping that community's identity and undergirded its religous experience from the start. Further, comparison with relevant texts from the Apocrypha and pseudepigrapha shows that the Qumran community represented a distinctive penitential movement in Second Temple Judaism.
Includes bibliographical references (pages 253-280) and indexes.
Keywords: Dead Sea scrolls; Repentance -- Judaism